Several criteria for judging H- and non-H-matrices. Issue 3 (3rd March 2016) - Liu, JianZhou; Wang, LeiLei; Lyu, Zhenhua
Abstract : In the paper, basing on the structure of Nekrasov matrices, the authors first obtain several practical criteria for judging H -matrices, then provide some criteria for identifying that a given matrix is not an H -matrix. The effectiveness of the proposed results is illustrated by numerical examples.